2019
DOI: 10.3389/fphar.2019.00817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mechanisms of Endothelial Cell Protections Between High-Density Lipoprotein and Apolipoprotein A-I Mimetic Peptide

Abstract: Apolipoprotein A-I (apoA-I) mimetic peptide, D-4F, exhibits anti-atherogenic effects similar to high-density lipoprotein (HDL). However, it remains elusive whether D-4F and HDL share similar molecular mechanisms underlying anti-atherogenic effects and endothelial cell protections. We here compared the metabolic changes in endothelial cells induced by D-4F and HDL against oxidized low-density lipoprotein (ox-LDL), which may be of benefit to understanding the protective mechanisms of HDL and D-4F. Functional ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
1
15
0
1
Order By: Relevance
“…Findings from our study show that metabolites involved in the glycerophospholipid metabolism pathway may also play a relevant role in pediatric hypertension. Glycerophospholipid metabolism pathway comprising two different routes, one toward phosphatidylethanolamine and the other toward phosphatidylcholine, has been shown to be a potential metabolic footprint of generation of reactive oxygen species in endothelial cells [ 27 ]. The disturbance of this pathway can trigger endothelial cell dysfunction and the development of atherosclerotic lesions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from our study show that metabolites involved in the glycerophospholipid metabolism pathway may also play a relevant role in pediatric hypertension. Glycerophospholipid metabolism pathway comprising two different routes, one toward phosphatidylethanolamine and the other toward phosphatidylcholine, has been shown to be a potential metabolic footprint of generation of reactive oxygen species in endothelial cells [ 27 ]. The disturbance of this pathway can trigger endothelial cell dysfunction and the development of atherosclerotic lesions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycerophospholipid metabolism pathway comprising two different routes, one toward phosphatidylethanolamine and the other toward phosphatidylcholine, has been shown to be a potential metabolic footprint of generation of reactive oxygen species in endothelial cells [ 27 ]. The disturbance of this pathway can trigger endothelial cell dysfunction and the development of atherosclerotic lesions [ 27 ]. In previous studies involving adult populations, phosphatidylethanolamine has been reported as a marker for hypertension, chronic kidney disease, and CVD [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, D-4F decreases the myocardial infarction area in hyperglycemia mice through promoting NO release and decreasing ROS generation in endothelial cells [167]. Metabolomic analysis showed that D-4F alleviates ox-LDL-induced oxidative stress and abnormal glycolysis in endothelial cells [168].…”
Section: Apoa-i Mimetic Peptidesmentioning
confidence: 99%
“…D-4F is one of the apoA-I mimetic peptides, which shares similar structure and function with native apoA-I and provides remarkable protection to endothelial cells ( Navab et al, 2010 ). The metabolomic analysis demonstrated that D-4F alleviates oxidized low-density lipoprotein (ox-LDL)–induced oxidative stress and abnormal glycolysis in endothelial cells ( Xu et al, 2019 ). D-4F promotes the activation of endothelial nitric oxide synthase (eNOS) and the generation of NO in coronary artery endothelial cells, thus protecting against ischemia/reperfusion injuries in mice ( Baotic et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%